Evaluation in Australasia: An Overview of Recent Developments - Wes Martz (The Evaluation Center at Western Michigan University, 2007)
Evaluation activities continue to develop throughout Australasia as evidenced by the Australasia Evaluation Society (AES) expanding its circle of influence and reaching out to its neighbors in Vietnam and China. Government officials and private sector personnel from these Asian neighbors visited Australia in October 2006 in an effort to learn more about evaluation in Australia.